The marine food web of the Malpelo Fauna and Flora Sanctuary, Colombia: a structural analysis from a topological approach - Colombo Estupiñán-Montaño; Alberto Sánchez-González; Felipe Galván-Magaña; Fernando R. Elorriaga-Verplancken; Manuel J. Zetina-Rejón; Carlos J. Polo-Silva (Theoretical Ecology, 2026)

Conversion of municipal biowaste into value-added products toward a circular bioeconomy: bridging the gap between laboratory-scale and full-scale implementation - José Manuel Alejandro Cerdán; Tatiana Kimura Kodama; G. H. D. Oliveira; Lucas Tadeu Fuess; Júlia Fonseca Colombo Andrade; Aldo Roberto Ometto (Clean Technologies and Environmental Policy, 2026)
Scaling-up municipal biowaste conversion technologies to industrial levels is essential for advancing clean and sustainable technologies and addressing significant technical, economic, and environmental challenges associated with urban organic waste management. Studies that explore technological gaps across the upstream, midstream, and downstream processing stages of biorefineries are critical for transforming biowaste into value-added products. This study aims to fill these gaps through a systematic literature review following the PRISMA guidelines and utilizing the Technology Readiness Level (TRL), which enabled the selection of 88 cases subsequently analyzed using descriptive and content analysis. The main findings show that anaerobic digestion has achieved full commercial maturity (TRL 9), while acidogenic fermentation remains mostly at TRL 6–7, and other pathways such as microbial protein or holocellulase production are still at early stages (TRL 3–4). High-value products, including polyhydroxyalkanoates (PHA) and succinic acid, are clustered at TRL 6–7, typically demonstrated at pilot scale, whereas hydrochar from hydrothermal carbonization has progressed up to TRL 8–9. Companies and projects confirm the feasibility of integrating biological, chemical, and thermal pathways into biorefineries, spanning a wide range of TRLs and showcasing their potential within the circular bioeconomy. Key gaps persist in scaling downstream processes for product purification, reducing costs, addressing feedstock variability, and optimizing pretreatment. By synthesizing experimental evidence with industrial demonstrations and sustainability assessments, this study provides a comprehensive perspective on how municipal biowaste can be converted into both non-fuel bioproducts and biofuels, thereby supporting circular bioeconomy strategies for future environmental policies. Graphical Abstract

Predicting acute developmental toxicity of chemicals in embryos of the African clawed frog (Xenopus laevis): Calibration and validation of regression-based quantitative structure activity relationship models for hazard assessment of chemicals in anuran amphibians - Christian Novello; Matteo Riccardo Di Nicola; Jean Lou CM Dorne; Erika Colombo; Edoardo Luca Viganò; Manuel E. Ortiz-Santaliestra; Nynke Kramer; Edoardo Carnesecchi; Anna Melina Steinbach; Ivano Eberini; Antony Williams; Emilio Benfenati; et al. (Toxicology Letters, 2026)

Distribution and fate of microplastics from the Chesapeake Bay to the Mid-Atlantic Bight: A Lagrangian particle tracking approach - Julia Abrao Teixeira; Piero L.F. Mazzini; Xun Cai; Manuel Colombo; Qubin Qin; Meredith Evans Seeley; Y. Joseph Zhang (Continental Shelf Research, 2026)

Enhanced H2O2 electrogeneration for simultaneous degradation of multiple pharmaceuticals and validation in real water using UVC-assisted processes - Raul José Alves Felisardo; Florymar Escalona Durán; Carlos Henrique Magalhães Fernandes; Géssica de Oliveira Santiago Santos; Renata Colombo; Manuel Andrés Rodrigo Rodrigo; Marcos Roberto de Vasconcelos Lanza (Chemical Engineering Journal, 2026)

Pre-Mesoproterozoic crustal framework and Mesoproterozoic evolution of the SW Angolan Shield: structural, geochemical, and isotopic insights from the Kunene Complex and surrounding basement - Enrique Merino-Martínez; Ezequiel Ferreira; Pablo Valverde-Vaquero; José Feliciano Rodrigues; Javier Escuder-Viruete; José Luis García-Lobón; Aratz Beranoaguirre; María del Carmen Feria; Carmen Rey-Moral; Paulo Bravo Silva; Pablo González-Cuadra; João Carlos Sousa; et al. (Precambrian Research, 2025)

Correction to: Ontogenetic feeding ecology of the silky shark (Carcharhinus falciformis) in the Colombian eastern tropical Pacific - Colombo Estupiñán‑Montaño; Daniel J. Villalobos‑Ramírez; Felipe Galván‑Magaña; Fernando R. Elorriaga‑Verplancken; Manuel J. Zetina-Rejón; Alberto Sánchez‑González; Carlos J. Polo‑Silva; Antonio Delgado‑Huertas (Environmental Biology of Fishes, 2025)

Ontogenetic feeding ecology of the silky shark (Carcharhinus falciformis) in the Colombian eastern tropical Pacific - Colombo Estupiñán-Montaño; Daniel J. Villalobos-Ramírez; Felipe Galván-Magaña; Fernando R. Elorriaga-Verplancken; Manuel J. Zetina-Rejón; Alberto Sánchez-González; Carlos J. Polo-Silva; Antonio Delgado-Huertas (Environmental Biology of Fishes, 2025)

Degradation of diethyl phthalate by photolysis of hydrogen peroxide electrogenerated using a Printex L6 carbon modified with Benzophenone cathode in an improved tangential flow cell - Taynara Oliveira Silva; Géssica de Oliveira Santiago Santos; Renata Colombo; Marcos Roberto de Vasconcelos Lanza; Manuel Andrés Rodrigo Rodrigo (Process Safety and Environmental Protection, 2024)

Zircon U-Pb and Lu-Hf isotopes reveal the crustal evolution of the SW Angolan Shield (Congo Craton) - Ezequiel Ferreira; Jérémie Lehmann; José Feliciano Rodrigues; Ben Hayes; Enrique Merino-Martínez; Lorenzo Milani; Grant M. Bybee; Trishya M. Owen‑Smith; José Luis García-Lobón; Colombo C. G. Tassinari; Henriette Ueckermann; Kei Sato; et al. (Gondwana Research, 2024)

Marine community trophic structure of Malpelo Island, Colombia from stable isotopes approach - Colombo Estupiñán-Montaño; Carlos J. Polo-Silva; Fernando R. Elorriaga-Verplancken; Alberto Sánchez-González; Manuel J. Zetina-Rejón; Antonio Delgado-Huertas; Jaiver Rojas-Cundumí; Felipe Galván-Magaña (Journal of Marine Systems, 2024)

Shelf-Basin Connectivity Drives Dissolved Fe and Mn Distributions in the Western Arctic Ocean: A Synoptic View into Polar Trace Metal Cycling - Laramie Jensen; Manuel Colombo (Oceanography, 2024)
There have been many changes over the past few decades in the physical environment and ecosystem health of the Arctic Ocean, which is a sentinel of global warming. Bioactive trace metal data of important micronutrients for algae across the global ocean, such as iron (Fe) and manganese (Mn), are key indicators of biogeochemical change. However, trace metal data in the Arctic have been historically sparse and generally confined to ice-free regions. In 2015, three major GEOTRACES expeditions sought to resolve trace metal distributions across the Arctic, covering the western, eastern, and Canadian Arctic sectors. The diverse Arctic shelves displayed unique controls on Fe and Mn cycling due to differing chemical, biological, and physical properties. Here, we contrast the shallow, reducing Chukchi Shelf in the western Arctic with the tidally forced, advective Canadian Arctic and the deeper, less productive Barents Shelf in the eastern Arctic. Reductive dissolution and physical resuspension both proved to be large sources of Fe and Mn to the Arctic and the North Atlantic outflow. In the isolated intermediate and deep waters, one-dimensional scavenging in the western and eastern Arctic contrasts with vertical biological signals in Baffin Bay and the Labrador Sea.

Control of particulate manganese (Mn) cycling in halocline Arctic Ocean waters by putative Mn‐oxidizing bacterial dynamics - Manuel Colombo; Julie LaRoche; Dhwani Desai; Jingxuan Li; Maria T. Maldonado (Limnology and Oceanography, 2023)
Particulate Mn, given its high adsorptive capacity and oxidation potential, has profound impacts on the cycling of various trace elements and organic matter in the ocean. Moreover, particulate Mn acts as a sink (via oxidation and adsorption) or as a source (via remineralization and photoreduction) term of bioactive dissolved Mn(II). In the Canadian Arctic Ocean, particulate Mn distributions in the water column revealed the presence of distinctively high particulate Mn concentrations and an overwhelming dominance of the non‐lithogenic component to the bulk particulate Mn pool. This phenomenon is of particular importance in halocline waters in the Canada Basin, the Canadian Arctic Archipelago and Baffin Bay, and near‐bottom samples in Baffin Bay. Enhanced microbially‐mediated Mn oxidation in the water column is suggested as the main mechanism driving the non‐lithogenic dominance. Indeed, the microbial community composition data associated with high non‐lithogenic particulate Mn (i.e., Mn oxides) display a high relative abundance of taxa (e.g., f.Pirellulaceae, o.Phycisphaerales, f.Cryomorphaceae, g. Moritella) that have been identified in Mn oxide enriched environments. Furthermore, numerous taxa identified in the Canada Basin halocline water, where non‐lithogenic particulate Mn peaked, are phylogenetically related to known (cultured) Mn‐oxidizing bacteria (MnOB; e.g., Rhodobacteraceae, Oceanospirillaceae, Rhizobiaceae, and other Alphaproteobacteria). Putative MnOB appears to proliferate in certain water masses having a unique set of environmental conditions: low light intensity—alleviating photoinhibition—and high dissolved Mn concentrations, the main drivers known to influence MnOB dynamic, and hence, Mn oxidation.

The paleoenvironmental and thermal histories of the Permian Irati Formation shale in the Paraná Basin, Brazil: An integrated approach based on mineralogical and organic imprints - Haline V. Rocha; Lucy G. Sant’Anna; Cristina F.A. Rodrigues; Márcia Mendes; Zélia Pereira; Gilda Lopes; Paulo Fernandes; Egberto Pereira; Colombo C.G. Tassinari; Manuel J. Lemos de Sousa (Marine and Petroleum Geology, 2023)

Emergence Response of Telenomus podisi (Hymenoptera: Scelionidae) to Field Temperature Originated from Colonies Reared at Different Temperature Regimes - Fernanda Caroline Colombo; Rodrigo Mendes Antunes Maciel; Matheus Deniz; Pedro Manuel Oliveira Janeiro Neves; Adeney de Freitas Bueno (Neotropical Entomology, 2023)

Trophic connectivity between the terrestrial and marine ecosystems of Malpelo Island, Colombia, evaluated through stable isotope analysis - Colombo Estupiñán-Montaño; Manuel J. Zetina-Rejón; Felipe Galván-Magaña; Antonio Delgado-Huertas; Fernando R. Elorriaga-Verplancken; Carlos J. Polo-Silva; Javier Rojas-Cundumí; Daniel J. Villalobos-Ramírez; Alberto Sánchez-González (Marine Biology, 2023)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Detrital zircon geochronology of the Cretaceous succession from the Iberian Atlantic Margin: palaeogeographic implications - Pedro A. Dinis; Jorge Dinis; Colombo Tassinari; Andy Carter; Pedro Callapez; Manuel Morais (International Journal of Earth Sciences, 2016)

Involvement of endothelial thromboxane A2 in the vasoconstrictor response induced by 15-E2t-isoprostane in isolated human umbilical vein - Federico Manuel Daray; Julia Renata Colombo; Julián Rodríguez Kibrik; Andrea Emilse Errasti; Facundo Germán Pelorosso; Wanda Nowak; Jean-Luc Cracowski; Rodolfo Pedro Rothlin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2006)